Akt/Protein Kinase B Inhibits Cell Death by Preventing the Release of Cytochrome c from Mitochondria - Kennedy, Scott G. (American Society for Microbiology, 1999)
Growth factors signaling through the phosphoinositide 3-kinase/Akt pathway promote cell survival. The mechanism by which the serine/threonine kinase Akt prevents cell death remains unclear. We have previously shown that Akt inhibits the activity of DEVD-targeted caspases without changing the steady-state levels of Bcl-2 and Bcl-x(L). Here we show that Akt inhibits apoptosis and the processing of procaspases to their active forms by delaying mitochondrial changes in a caspase-independent manner. Akt activation is sufficient to inhibit the release of cytochrome c from mitochondria and the alterations in the inner mitochondrial membrane potential. However, Akt cannot inhibit apoptosis induced by microinjection of cytochrome c. We also demonstrated that Akt inhibits apoptosis and cytochrome c release induced by several proapoptotic Bcl-2 family members. Taken together, our results show that Akt promotes cell survival by intervening in the apoptosis cascade before cytochrome c release and caspase activation via a mechanism that is distinct from Bad phosphorylation.